2009
DOI: 10.1080/00365520903121685
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclooxygenase-2, glucose transporter-1 and angiogenesis in gallbladder carcinomas and their impact on prognosis

Abstract: Next to age and gender of patients, hypoxia of gallbladder tumours is a factor influencing survival. Among hypoxic factors, GLUT-1 expression is an important (significant) denominator of poor prognosis in gallbladder carcinomas, but not COX-2 nor angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…All of the included studies measured the expression of GLUT1 by means of immunohistochemistry (IHC) staining or PCR in human tissues, and the cut-off values varied across studies. Among the studies, 4 evaluated lung cancer [58], 3 evaluated pancreatic cancer [911], 3 evaluated breast cancer [12, 14], 2 evaluated gallbladder cancer [10, 15], 2 evaluated gastric cancer [16, 17], 2 evaluated colorectal cancer [18, 19], 2 evaluated laryngeal cancer [20, 21], and 1 each evaluated hypopharyngeal cancer [22], endometrial cancer [23], salivary gland tumor [24], adrenocortical cancer [25], liver cancer [26], ampulla of Vater cancer [10], extrahepatic bile duct cancer [10], oral cancer [27], neuroblastic tumors [28], cervical cancer [29], ovarian cancer [30] and esophageal cancer [31]. Due to the retrospective design of the included studies, only five studies examined both OS and DFS [6, 12, 14, 25, 29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the included studies measured the expression of GLUT1 by means of immunohistochemistry (IHC) staining or PCR in human tissues, and the cut-off values varied across studies. Among the studies, 4 evaluated lung cancer [58], 3 evaluated pancreatic cancer [911], 3 evaluated breast cancer [12, 14], 2 evaluated gallbladder cancer [10, 15], 2 evaluated gastric cancer [16, 17], 2 evaluated colorectal cancer [18, 19], 2 evaluated laryngeal cancer [20, 21], and 1 each evaluated hypopharyngeal cancer [22], endometrial cancer [23], salivary gland tumor [24], adrenocortical cancer [25], liver cancer [26], ampulla of Vater cancer [10], extrahepatic bile duct cancer [10], oral cancer [27], neuroblastic tumors [28], cervical cancer [29], ovarian cancer [30] and esophageal cancer [31]. Due to the retrospective design of the included studies, only five studies examined both OS and DFS [6, 12, 14, 25, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the retrospective design of the included studies, only five studies examined both OS and DFS [6, 12, 14, 25, 29]. Sixteen studies investigated the association between GLUT1 level and OS [711, 1521, 24, 27, 28, 30], while four studies investigated the association between GLUT1 and DFS [5, 13, 23, 26]. Studies by Mineta [22] reported relapse-free survival data, whereas study by Sawayama [31] reported data of relapse-free survival and cancer-specific survival.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Glut-1 expression has been associated with a poor prognosis in gallbladder cancer [19], oral SC [20], SC of the tongue [21], pancreatic cancer [22], and soft tissue sarcoma [23], and the association between HIF1α and poor prognosis has been reported in breast cancer [24][25][26], nonsmall cell lung cancer [27], nasopharyngeal carcinoma [28], esophageal SC [29], and laryngeal SC [30]. In addition, COX2 expression has been associated with a poor prognosis in laryngeal SC [30] and nasopharyngeal carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with tumors that showed strong GLUT-1 expression had a significantly shorter survival time than GLUT-1 Immunoreactivity of the Gallbladder patients whose tumors showed negative, weak or moderate GLUT-1 expression (6.3±7.0 months vs. 17.7±22.4 months, p<0.001) [19].…”
Section: Resultsmentioning
confidence: 99%